Pengembangan Media Pembelajaran Game Edukasi pada Materi Panca Indra Manusia Kelas IV SDN 21 Bunga Pasang - Kahilah, Natasha Dwi; Anugrah, Septriyan; Hendri, Nofri; Kurnia, Reni (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research is motivated by the low level of students’ understanding of the human five senses material due to the limited availability of interactive learning media. Teachers still rely on traditional lectures and conventional media, resulting in low student engagement and difficulty in grasping the material. The aim of this study is to develop an interactive educational game as a learning medium to improve the understanding of fourth-grade students at SDN 21 Bunga Pasang. This study uses the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). The research stages include needs analysis, design, expert validation, limited trials, and product dissemination. The media was developed using Construct 2 and accessed via Chromebook. Data were collected through validation questionnaires, practicality assessments, and effectiveness tests, then analyzed both quantitatively and qualitatively. The results show that the media is highly valid with an average score of 4.93 from the material expert, and 4.10 and 4.53 from two media validators. The practicality reached 90.9% (very practical), and the effectiveness test yielded an N-Gain score of 71.83% (moderately effective). Therefore, the educational game media is considered feasible, practical, and reasonably effective in enhancing students’ understanding of the human five senses material